2013
DOI: 10.1159/000351757
|View full text |Cite
|
Sign up to set email alerts
|

Renal Impairment and Clinical Outcomes of <i>Clostridium difficile</i> Infection in Two Randomized Trials

Abstract: Background/Aims: Patients with chronic kidney disease (CKD) have increased risk for Clostridium difficile infection (CDI) and for subsequent mortality. We determined the effect of CKD on response to treatment for CDI. Methods: This is a post hoc analysis of two randomized controlled phase 3 trials that enrolled patients with CDI. Patients received either fidaxomicin 200 mg b.i.d. or vancomycin 125 mg q.i.d. for 10 days. Univariate and multivariate analyses compared end points by treatment received and CKD stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 52 publications
4
35
0
Order By: Relevance
“…All the characteristics of the Markov model have been extensively described in the assessment reports by the Welsh and Scottish authorities in the United Kingdom [18,19], as well as in several publications [17,20,21]. Patients in the model were treated orally with fidaxomicin [200 mg twice daily (BID) for 10 days] or vancomycin [125 mg four times daily (QID) for 10 days] [3][4][5]18]. All patients initially had CDI and, following treatment, were either clinically cured or not clinically cured (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the characteristics of the Markov model have been extensively described in the assessment reports by the Welsh and Scottish authorities in the United Kingdom [18,19], as well as in several publications [17,20,21]. Patients in the model were treated orally with fidaxomicin [200 mg twice daily (BID) for 10 days] or vancomycin [125 mg four times daily (QID) for 10 days] [3][4][5]18]. All patients initially had CDI and, following treatment, were either clinically cured or not clinically cured (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Data on the effectiveness of the antibiotics in the treatment of CDI and the main probabilities of transition between health states used in the model were obtained from the clinical trial publications that reported the results in the specific populations studied [3][4][5] and from other published sources [1,2,[31][32][33][34][35] (Table 3). Quality-adjusted life-years (QALYs) for the CDI patients were calculated from utilities obtained from Slobogean et al…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of previous studies assessing the risk of CDAD in patients with CKD and end-stage renal disease (ESRD), however, are conflicting. Several studies have shown that a history of CKD or ESRD is significantly associated with incident and recurrent CDAD [7,[9][10][11][12][13][14][15][16][17]. Conversely, a number of studies have shown no significant increased risk of incident and recurrent CDAD in patients with CKD or ESRD [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%